2015
DOI: 10.1002/tesq.222
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Better Time to Focus on Form? Teacher and Learner Views

Abstract: This study investigated the views of teachers and learners regarding the timing of grammatical instruction, conceptualized as a distinction between isolated and integrated form‐focused instruction (FFI) proposed by Spada and Lightbown (2008). Both types of FFI are described as taking place in primarily meaning‐based communicative classrooms. They differ in that isolated FFI occurs separately from communicative activities, whereas integrated FFI occurs during communicative activities. Using this theoretical dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
2
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 42 publications
3
37
2
2
Order By: Relevance
“…The results obtained suggest that teachers could employ (or continue to employ) phonetic notation in explicit pronunciation teaching (at least at tertiary education level). This they can do in both isolated and integrated focus-on-form instruction (in primarily meaningbased communicative classrooms), given that although learners seem to prefer integrated focus-on-form instruction, they also acknowledge the value of isolated focus-on-form instruction (Valeo & Spada, 2015). The use of phonetic notation, however, requires addressing a number of issues that teachers should also bear in mind.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results obtained suggest that teachers could employ (or continue to employ) phonetic notation in explicit pronunciation teaching (at least at tertiary education level). This they can do in both isolated and integrated focus-on-form instruction (in primarily meaningbased communicative classrooms), given that although learners seem to prefer integrated focus-on-form instruction, they also acknowledge the value of isolated focus-on-form instruction (Valeo & Spada, 2015). The use of phonetic notation, however, requires addressing a number of issues that teachers should also bear in mind.…”
Section: Resultsmentioning
confidence: 99%
“…Learner views have recently been a common focus of research as they are factors affecting the learning process (Kalaja & Barcelos, 2003, 2013. Some projects have also focused on areas related to pronunciation, for example on model accents (Dalton-Puffer, Kaltenboeck, & Smit, 1997), pronunciation difficulties (Derwing & Rossiter, 2002), amount of earlier pronunciation instruction (Tergujeff, 2013), usefulness of formal instruction (Cenoz & García-Lecumberri, 1999) or views on 'focus on form' instruction (Valeo & Spada, 2015). Derwing and Rossiter (2002), for example, looked at ESL (English as a second language) learners' perceptions of their pronunciation difficulties and strategies they employed when faced with communication breakdown.…”
Section: Learner's Views Of Pronunciation Instruction and Phonetic Nomentioning
confidence: 99%
“…In another study by Valeo and Spada (2016), teachers and learners were found to prefer integrated FFI over I-FFI for the teaching and learning of grammar. Using questionnaires, the researchers explored the teachers and learners' views on the values of integrated and isolated FFI in two contexts, ESL in Canada and EFL in Brazil.…”
Section: Empirical Research On Focus On Form Instructionsmentioning
confidence: 95%
“…One of the main issues in communicative language teaching (CLT) is the treatment on grammar in the classrooms (Valeo & Spada, 2016;Ellis, 2008;Spada, 2007). Ellis, Basturkmen & Loewen's (2002) discuss 'focus-on-form' (FoF) which refers to "… the treatment of linguistic form in the context of performing a communicative task" (p. 1).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years I have carried out research to investigate different aspects of isolated and integrated FFI. This includes studies to explore teacher and learner preferences for the two types of instruction (Valeo and Spada, 2015;Spada and dos Santos Lima, 2015) as well the contributions of isolated and integrated FFI to L2 learning (Spada et al, 2014).…”
Section: Msl and Pcb: How Do You Define Form-focused Instruction (Ffi)?mentioning
confidence: 99%